The Future of Flying Base Stations: Empirical and Numerical Investigations of mmWave-Enabled UAVs - Ryunosuke Masaoka; Gia Khanh Tran; Jin Nakazato; Kei Sakaguchi (Future Internet, 2023)
Nowadays, wireless communications are ubiquitously available. However, as pervasive as this technology is, there are distinct situations, such as during substantial public events, catastrophic disasters, or unexpected malfunctions of base stations (BSs), where the reliability of these communications might be jeopardized. Such scenarios highlight the vulnerabilities inherent in our current infrastructure. As a result, there is growing interest in establishing temporary networks that offer high-capacity communications and can adaptively shift service locations. To address this gap, this paper investigates the promising avenue of merging two powerful technologies: Unmanned Aerial Vehicles (UAVs) and millimeter-wave (mmWave) transmissions. UAVs, with their ability to be operated remotely and to take flight without being constrained by terrestrial limitations, present a compelling case for being the cellular BSs of the future. When integrated with the high-speed data transfer capabilities of mmWave technology, the potential is boundless. We embark on a hands-on approach to provide a tangible foundation for our hypothesis. We carry out comprehensive experiments using an actual UAV equipped with an mmWave device. Our main objective is to meticulously study its radio wave propagation attributes when the UAVs are in flight mode. The insights gleaned from this hands-on experimentation are profound. We contrast our experimental findings with a rigorous numerical analysis to refine our understanding. This comparative study aimed to shed light on the intricacies of wave propagation behaviors within the vast expanse of the atmosphere.